THE RISK OF SKIN IRRITATION OF CLARTÉ IN EXPERIMENTAL RABBITS - Phan, Hong Minh (Tạp chí Sinh lý học Việt Nam, 2024)
CLARTÉ is an external genital hygiene product, thus assessing skin irritation is an important test before commercializing the product for the community. Objectives: The study evaluated the local irritation on healthy rabbit skin of CLARTÉ manufactured and supplied by VIHECO PHARMA., JSC. Methods: The study was conducted according to the guidelines of the Vietnam Ministry of Health, ISO 10993-10, and OECD on skin irritation assessment for topical products. Three healthy white New Zealand rabbits were shaved off the fur on the back. Animals were applied directly 0.5 mL of CLARTÉ solution on the back skin and covered the application sites with a 2,5 cm × 2,5 cm non-occlusive dressing for 4 hours. We evaluated the irritation index including erythema and edema on the skin at 1, 24, 48, and 72 hours after removing the patches. Results: Three rabbits were still healthy, and living normally. There was very slight or well-defined erythema and very slight edema on the rabbit's skin applied by CLARTÉ after the first 24-hour treatment. The irritation index of CLARTÉ was 0.44, corresponding to negligible skin irritation during 72 hours of continuous monitoring. Conclusions: CLARTÉ product applied topically caused negligible irritation on healthy rabbit skin.